Financial frictions and the reaction of stock prices to monetary policy shocks - Ali Ozdagli (Federal Reserve Bank of Boston, 2014)
This paper reveals and tests a new theoretical implication of the credit channel of monetary policy: as financial frictions (monitoring or auditing costs) increase, the reaction of stock prices to monetary policy shocks decreases. Correspondingly, towards the end of the Enron accounting scandal, the stock prices of firms sharing the same auditor as Enron responded by about 50 to 60 basis points less than other firms to a 10 basis point reduction in the federal funds target rate. This effect is particularly strong among more opaque firms for which financial statements likely provide a more important monitoring tool.
Keywords: G32; G12; E44; E52; 330; financial constraints; stock market; credit channel; monetary policy